Targeting Pseudomonas aeruginosa quorum sensing with sodium salicylate modulates immune responses in vitro and in vivo - Gerner, Erik; Giraldo-Osorno, Paula Milena; Johansson Loo, Anna; Firdaus, Rininta; Ben Amara, Heithem; Werthén, Maria; Palmquist, Anders; Thomsen, Peter; Omar, Omar; Almqvist, Sofia; Trobos, Margarita (Frontiers in Cellular and Infection Microbiology, 2023)
Chronic infections are a major clinical challenge in hard-to-heal wounds and implanted devices. Pseudomonas aeruginosa is a common causative pathogen that produces numerous virulence factors. Due to the increasing problem of antibiotic resistance, new alternative treatment strategies are needed. Quorum sensing (QS) is a bacterial communication system that regulates virulence and dampens inflammation, promoting bacterial survival. QS inhibition is a potent strategy to reduce bacterial virulence and alleviate the negative impact on host immune response. This study investigates how secreted factors from P. aeruginosa PAO1, cultured in the presence or absence of the QS inhibitor sodium salicylate (NaSa), influence host immune response. In vitro, THP-1 macrophages and neutrophil-like HL-60 cells were used. In vivo, discs of titanium were implanted in a subcutaneous rat model with local administration of P. aeruginosa culture supernatants. Host immune response to virulence factors contained in culture supernatants (+/-NaSa), was characterized through cell viability, migration, phagocytosis, gene expression, cytokine secretion, and histology. In vitro, P. aeruginosa supernatants from NaSa-containing cultures significantly increased THP-1 phagocytosis and HL-60 cell migration compared with untreated supernatants (-NaSa). Stimulation with NaSa-treated supernatants in vivo resulted in: (i) significantly increased immune cell infiltration and cell attachment to titanium discs; (ii) increased gene expression of IL-8, IL-10, ARG1, and iNOS, and (iii) increased GRO- protein secretion and decreased IL-1β, IL-6, and IL-1 secretion, as compared with untreated supernatants. In conclusion, treating P. aeruginosa with NaSa reduces the production of virulence factors and modulates major immune events, such as promoting phagocytosis and cell migration, and decreasing the secretion of several pro-inflammatory cytokines.